Lithium-doped calcium silicate cement regulates the immune microenvironment and promotes M2 macrophage polarization for enhancing bone regeneration - Yen-Hong Lin; Cheng-Yu Chen; Kun-Hao Chen; Ting-You Kuo; Tsung-Li Lin; Ming-You Shie (Journal of Biological Engineering)
Abstract Bone defects present a significant challenge in orthopedics and trauma surgery, necessitating innovative approaches to stimulate effective bone regeneration. This study investigated the potential of lithium-doped calcium silicate (LiCS) cement to enhance bone regeneration and modulate the immune microenvironment to promote tissue repair. We synthesized a LiCS ceramic powder and performed comprehensive analyses of its physicochemical properties, including phase composition, morphology, setting time, and mechanical strength. The results demonstrated that the incorporation of lithium into calcium silicate significantly increased the diametral tensile strength (DTS) and facilitated hydroxyapatite formation compared with undoped calcium silicate. In vitro assays revealed that the LiCS cement enhanced the proliferation, adhesion, and spread of Wharton’s jelly mesenchymal stem cells (WJMSCs). Additionally, Li-CS cement exhibited remarkable immunomodulatory properties by reducing pro-inflammatory cytokines and increasing anti-inflammatory cytokines, promoting the polarization of macrophages towards the M2 phenotype. The presence of Li in the cement also significantly improved the osteogenic differentiation of WJMSCs, as evidenced by elevated levels of alkaline phosphatase and osteocalcin expression. These findings underscore the dual functional capabilities of the LiCS cement in enhancing osteogenesis and modulating the immune environment, making it a promising material for bone tissue engineering and regeneration.